PENERAPAN MEDIA PEMBELAJARAN BERBASIS ASSEMBLR EDU DALAM MATA PELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 1 ULAWENG - Kartini Tawa; Romi Adiansyah; Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to analyze the improvement of students’ learning outcomes in science through the use of Assemblr Edu-based learning media for eighth-grade students of SMP Negeri 1 Ulaweng, Bone Regency. The research employed a Classroom Action Research (CAR) approach that is practical in nature and was carried out in two cycles. Each cycle consisted of four main stages: planning, action implementation, observation, and reflection. The research subjects were 32 students of class VIII C in the first semester of the 2025/2026 academic year. Data were collected through learning achievement tests, observations of teacher and student activities, and supporting documentation. The learning achievement tests were administered in the form of pre-tests and post-tests to measure students’ comprehension improvement after the application of Assemblr Edu media based on Augmented Reality (AR). The results revealed that the use of Assemblr Edu media had a significant impact on improving students’ learning outcomes. The average pre-test score was 39.06 with a mastery level of 0%. After the implementation up to Cycle II, the average score increased to 79.84, with a 100% mastery rate, indicating that all students achieved the Minimum Mastery Criteria (KKM ≥ 70). In addition to cognitive improvement, students also showed enhanced learning engagement, reflected in their active participation in discussions, group collaboration, and effective use of learning media. Based on these findings, it can be concluded that the implementation of Assemblr Edu-based learning media is effective in improving both learning outcomes and learning activities of eighth-grade students of SMP Negeri 1 Ulaweng, Bone Regency, in science subjects.